Estimating Demand for IMF Financing by Low-Income Countries in Response to Shocks - Bal Gunduz, Yasemin (IMF Working Papers; Working Paper ;, 2009)
This paper estimates factors affecting demand for Fund financing by Low-Income Countries (LICs) in response to policy and exogenous shocks. Various economic variables including reserve coverage, current account balance to GDP, real GDP growth, macroeconomic stability, and terms of trade shocks are found to be significant determinants of Fund financing. Moreover, global conditions, including changes in real oil and non-oil commodity prices and world trade, are also significant. Therefore, the demand for Fund financing by LICs is likely to be cyclical in response to common shocks with its intensity depending on the severity and persistence of adverse shocks.